Correlation between premonitory urges and tic symptoms in a Chinese population with tic disorders - Yi Gu; Ying Li; Yonghua Cui (Wiley, 2020)
ABSTRACT Importance Tics usually start around 4-6 years old and affect about 1% of school‐age children. Premonitory urges (PUs) are sensory phenomena that precede tics and are often described as unpleasant feelings. Recent evidence supports a relationship between PUs and tic severity, but reports are conflicting. In addition, there is no report of PUs in the Chinese population. Objective To investigate the correlation between PUs and tic symptoms in the Chinese population with tic disorders. Methods We recruited 252 Chinese individuals with chronic tic disorders (age 5-16 years). The Yale Global Tic Severity Scale (YGTSS) was used to assess tic symptoms, and the Premonitory Urge for Tics Scale (PUTS) was used to assess PUs. We calculated Spearman correlations between PUTS and YGTSS scores, and constructed a linear regression model to predict the tic symptom severity by PUs. Results There was a significant positive correlation between PU severity (PUTS scores) and motor tic severity, total tic severity, tic‐caused impairment (YGTSS scores) (P < 0.05). PU severity was a significant positive predictor of tic symptom severity (standardized beta coefficient = 0.174, t = 2.786, P = 0.006). Interpretation We provide evidence for a correlation between PUs and tic symptoms. PU severity predicts tic symptom severity. Further research on PUs is needed to clarify the shared brain mechanism with tics, and their role in tic expression. A suitable tool to assess PUs in younger children is also needed.